New species of Acasta and Balanus (Balanoidea: Acastinae, Balaninae) from the Early Miocene (Burdigalian) of the Aquitaine Basin, France - Carriol, René-Pierre; Cahuzac, Bruno; Lesport, Jean-François (Zootaxa, 2011)
Two new species of spiny barnacles (Balanoidea: Acastinae, Balaninae) are described from the lower Burdigalian (Early Miocene) of the Aquitaine Basin, southwest France. The first, Acasta martillacensis sp. nov., from Martillac, is characterised by a shell with internal longitudinal ribs, a cellular space between the sheath and wall, a carinal sheath which adheres to the wall in the centre of its basal edge, a cup-shaped basis and a scutum with radial striae externally and a less than prominent adductor ridge internally. The second, Balanus aculeatus sp. nov., from Saucats (Le Péloua), has paries exteriorly with strong, tubular spines. An overview of outcrops of Burdigalian strata in the area, within a palaeogeographic context, is added.